Rapid cultivation and enrichment of anammox bacteria solely using traditional activated sludge as inoculum and biocarrier in low-strength real sewage treatment. (August 2022) - Gong, Xiaofei; Zhang, Liang; Gong, Qingteng; Liu, Xuefan; Li, Xiyao; Zhang, Qiong; Peng, Yongzhen
Graphical abstract: Highlights: A short 8.5-day doubling time of AnAOB was achieved using low-ammonia real sewage. Specific anammox activity augmented to 1.85 mg N·g VSS −1 ·h −1 from trace value. Large-flocs harbored the highest AnAOB abundance and nitrogen removal capacity. Excellent efficiency was achieved with inf.TIN and eff.TIN of 55.3 and 4.1 mg·L −1 . Activated sludge as inoculum and biocarrier promoted AnAOB growth and retention. Abstract: In low-ammonia sewage anammox process, cultivation and enrichment of anammox bacteria (AnAOB) is a challenge especially from traditional activated sludge. To this end, a novel strategy solely using activated sludge as inoculum and biocarrier in a dynamic fixed-bed reactor was proposed in this study. During 115-day operation, excellent performance was achieved with influent total inorganic nitrogen (TIN) and effluent TIN of 55.3 mg·L −1 and 4.1 mg·L −1, respectively. Rapid enrichment of AnAOB (doubling time: 8.5 days) was demonstrated by augmented specific anammox activity (trace value to 1.85 mg N·g VSS −1 ·h −1 ) and increased hzsB gene number (10 6 to 10 9 copies·g −1 dry sludge), with predominance of Candidatus_Brocadia . Large-flocs aggregate was the primary habitat for AnAOB with highest abundance and capacity. The distinctive sludge properties, symbiotic microbial interactions and dynamic operation scheme facilitated AnAOB growth and retention. This study provides a simple, economic and workable approach for the start-up of mainstream anammox process.